Pengaruh Locus of Control, Financial Technology, dan Tingkat Pendidikan terhadap Perilaku Keuangan Pelaku UMKM Sektor Jasa di Kota Padang - Kartika Kartika; Elsa Meirina; Teguh Hidayat; Dewi Zulvia; Desyani Umar (Universitas Galuh, 2026)
This study aims to analyze the effect of locus of control, financial technology utilization, and education level on the financial behavior of service sector MSME actors in Padang City. The problem in this study is the low level of financial management in MSMEs and the inconsistency of previous research results. The study used a quantitative approach with a sample of 85 MSME actors selected using convenience sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 26. The results showed that financial technology and education level affect financial behavior, while locus of control has no effect. Simultaneously, all three variables have a significant effect on financial behavior with an R² value of 25.5%. The conclusion of this study is that access to technology and education are more dominant than internal psychological factors in shaping the financial behavior of service sector MSME actors in Padang City.